Maintenance of Remission and Risk of Relapse in Myeloperoxidase-Positive ANCA-Associated Vasculitis with Kidney Involvement. Issue 1 (January 2023) - Casal Moura, Marta; Specks, Ulrich; Tehranian, Shahrzad; Sethi, Sanjeev; Zubidat, Dalia; Nardelli, Luca; dos Santos, Fernanda G.; Sousa, Ciria; León-Róman, Juan; Bobart, Shane A.; Greene, Eddie; Zand, Ladan; et al.
Visual Abstract: Abstract : Background: The optimal strategy for remission-maintenance therapy in patients with myeloperoxidase-ANCA (MPO-ANCA)–associated vasculitis is not established. Defining parameters to guide maintenance therapy is required. Methods: This was a retrospective cohort study of all patients with MPO-ANCA–associated vasculitis (microscopic with polyangiitis and granulomatosis with polyangiitis) and GN followed at the Mayo Clinic between 1996 and 2015. Relapse rate, MPO-ANCA status, and remission-maintenance therapies were reviewed. Logistic regression models, Kaplan–Meier method, and Cox proportional hazards regression models were applied. Results: We analyzed 159 patients with active MPO-ANCA–associated vasculitis with GN. Sixty-six (42%) patients had at least one relapse, and 52 (33%) relapsed before 60 months. Patients with MPO-ANCA who became persistently negative did not relapse (hazard ratio [HR], 0.03; 95% confidence interval [95% CI], 0.002 to 0.431; P =0.01). The reappearance of MPO-ANCA was associated with a higher risk of relapse (HR, 1.91; 95% CI, 1.109 to 3.293; P =0.02). Immunosuppression was withdrawn in 80 (50%) patients, and this was less likely in those who received cyclophosphamide for remission induction or in patients with persistently positive MPO-ANCA (odds ratio [OR], 0.44; 95% CI, 0.228 to 0.861; P =0.02 and OR, 0.42; 95% CI, 0.213 to 0.820; P =0.01, respectively). Relapse frequency was not different between patients with persistently positive MPO-ANCA and patients with MPO-ANCA reappearance (44% versus 39%, P =0.49), irrespective of remission-maintenance treatment. Ear, nose, and throat involvement (OR, 6.10; 95% CI, 1.280 to 29.010; P =0.02) and MPO-ANCA reappearance (OR, 9.25; 95% CI, 3.126 to 27.361; P <0.001) were independently associated with relapse after treatment withdrawal. Conclusions: Patients persistently MPO-ANCA negative are at low risk for relapse even without remission-maintenance therapy. Persistence or subsequent reappearance of MPO-ANCA is associated with a higher risk of relapse. Podcast: This article contains a podcast at https://dts.podtrac.com/redirect.mp3/www.asn-online.org/media/podcast.aspx?p=CJASN&e=2023_01_10_CJN06460622.mp3